Availability and Pharmacoeconomics of Insulin Therapy in Countries with the Largest Number of Diabetics - S. V. Ponomarenko (Фармакоэкономика)
The aim of the review was to analyze the availability of insulin therapy and the ways to improve it in countries with the largest number of patients with diabetes. It was also aimed to assess the medical, social and economic importance of insulin therapy and industrial production of therapeutic recombinant insulin.Materials and methods. The analysis was based on the data taken from monographs and publications in peer-reviewed journals, reports of companies and medical organizations, and the information available in the Internet. The demand and supply in the market of recombinant therapeutic insulin, the insulin market segmentation, and the costs for insulin replacement therapy in countries with the largest number of patients with diabetes were studied. Results and discussion. The pro- and contra- arguments regarding the import of insulin and its impact on the national budget are presented. Technological specifics of recombinant insulin production are discussed; the funding and investments in the biopharmaceutical sector are analyzed. The benefits of industrial production of recombinant therapeutic insulin and its impact on the regional and national economy are demonstrated.Conclusion. The availability of therapeutic insulin in most countries with the largest number of diabetics is unsatisfactory and needs a radical improvement. By analyzing the economic aspects of diabetes and the pharmacoeconomics of insulin, it is advised to develop a modern management system for insulin replacement therapy, especially in countries with large numbers of diabetics. The use of innovative technologies will reduce the production costs of recombinant therapeutic insulin, increase the availability of insulin therapy and thereby improve the quality of life in diabetic patients. Evidence that the production of therapeutic insulin has a positive effect not only on the healthcare, but on the socio-economic situation in the region is also provided. Countries with a number of diabetics exceeding 5 million are encouraged to launch their own production of recombinant therapeutic insulin. The results of the present analysis confirm that half of them are able to manufacture adequate human insulin and/or its analogues.